2005
DOI: 10.4049/jimmunol.174.2.727
|View full text |Cite
|
Sign up to set email alerts
|

The Reciprocal Interaction of NK Cells with Plasmacytoid or Myeloid Dendritic Cells Profoundly Affects Innate Resistance Functions

Abstract: A reciprocal activating interaction between NK cells and dendritic cells (DC) has been suggested to play a role in the functional regulation of these cells in immunity, but it has been studied only using in vitro generated bone marrow- or monocyte-derived DC. We report that human peripheral blood plasmacytoid DC (pDC) and myeloid DC are necessary to induce NK cell function depending on the type of microbial stimulus. pDC and myeloid DC are required for strongly increased NK cytolytic activity and CD69 expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

33
374
3
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 344 publications
(411 citation statements)
references
References 52 publications
33
374
3
1
Order By: Relevance
“…These results suggested that soluble factors from infected DCs might contribute to increasing CD69 expression by NK cells. Whereas addition of neutralizing anti-IL-12 or anti-IFN-␣ to the culture had no affect on CD69 expression (data not shown), a mixture of anti-type I IFNs reduced CD69 up-regulation, as previously observed (19). Although CD69 expression was further reduced by including Abs against type I IFNs, NKG2D, and NKp46 in the culture, complete abrogation of CD69 expression was never achieved.…”
Section: Nk Cell Up-regulation Of Cd69 Involves Nkg2d Nkp46 and Typsupporting
confidence: 72%
See 2 more Smart Citations
“…These results suggested that soluble factors from infected DCs might contribute to increasing CD69 expression by NK cells. Whereas addition of neutralizing anti-IL-12 or anti-IFN-␣ to the culture had no affect on CD69 expression (data not shown), a mixture of anti-type I IFNs reduced CD69 up-regulation, as previously observed (19). Although CD69 expression was further reduced by including Abs against type I IFNs, NKG2D, and NKp46 in the culture, complete abrogation of CD69 expression was never achieved.…”
Section: Nk Cell Up-regulation Of Cd69 Involves Nkg2d Nkp46 and Typsupporting
confidence: 72%
“…NK cells are particularly implicated in defense against viral infections, which they provide through killing of infected cells and the production of cytokines, notably IFN-␥ (13)(14)(15). Although recent studies have emphasized the role of DCs in promoting adaptive immune responses to influenza (16 -18), less has been said of the part played by NK cells and NK-DC cooperation (19).…”
Section: Nkp46 and Nkg2d Recognition Of Infected Dendritic Cells Is Nmentioning
confidence: 99%
See 1 more Smart Citation
“…Another factor in HIV-1 disease progression and immune system dysfunction is related to excessive immune activation (47)(48)(49). In HIV-1 infection, dysregulation of inflammatory responses points to the importance of studying critical molecules such as COX-2, which contributes to the pathogenesis of diseases with uncontrolled or chronic inflammation (50,51).…”
Section: Discussionmentioning
confidence: 99%
“…18 As a first defense, NK cells and other innate lymphocytes play an essential role in the inhibition of tumorigenesis, tumor growth, and tumor metastasis. [19][20][21] We and other researchers previously demonstrated that dendritic cell (DC) therapy increases the activation of NK cells against tumor cells [22][23][24] and that CD1d C cells loaded with invariant NKT cell ligand generate NKT cell-mediated protection against tumor cells. 25 Although there are reports in tumor-bearing mice of interactions between NK cells and various types of myeloid cells, i.e., DCs, macrophages, MDSCs, it is unclear whether NK cells influence the number or function of MDSCs.…”
Section: Introductionmentioning
confidence: 99%